Odpowiedzi

Najlepsza Odpowiedź!
2010-01-07T09:43:05+01:00
A.
3-2(x-3)(x+2)=-2x²-2x
3 - 2(x² + 2x - 3 x - 6) = - 2x² - 2x
3 - 2x² - 4x + 6x + 12 = -2x² - 2x
-2x² + 2x² - 4x + 2x = -15
-2x = -15/ :(-2)
x = 7,5
B.
3(x-3)(x+2)=3x²+7x
3 (x² + 2x - 6x -6) = 3x² + 7x
3x² + 6x - 18x - 18 = 3x² + 7x
3x² - 3x² + 6x - 7x = 18
-x = 18 / *(-1)
x = 18
C.
2-1+x/2=2x-1/3/ * 6
3 (2-1+x) = 2 *(2x-1)
6 - 3 + 3x = 4x - 2
3x - 4x = -2 - 3
-x = -5 / *(-1)
x = 5

D.
3+1+x/3=2x-1/5 / * 15
5 *(3+1+x) = 3 * (2x-1)
15 + 5 + 5x = 6x - 3
5x - 6x = - 3 - 20
- x = - 23 /* (-1)
x = 23
1 5 1